Implementation of the Yanbu'a Method in Qur'anic Learning: A Case Study at Jarinabi Islamic Boarding School - Nita Novita Sari; Gusli Bambang Irawan (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This study aims to analyze the implementation of the Yanbu'a method in Qur'anic learning at Jarinabi Islamic Boarding School, East Tanjung Jabung, and to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative case study approach. Data were collected through observations, semi-structured interviews, and documentation involving one principal, two Qur'anic teachers, and eight students. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification, while trustworthiness was established through source and methodological triangulation. The findings indicate that the Yanbu'a method is implemented systematically through sequential instruction, individualized guidance, continuous practice, and ongoing assessment, enabling students to progressively develop their Qur'anic recitation competence. Its successful implementation is supported by teachers' competencies, students' learning motivation, parental involvement, and a conducive learning environment, whereas differences in students' initial abilities, limited instructional time, and inconsistent practice outside the classroom remain major challenges. This study highlights that the effectiveness of the Yanbu'a method depends on the integration of pedagogical, social, and environmental factors rather than instructional procedures alone. These findings provide practical insights for Islamic educational institutions in strengthening systematic and sustainable Qur'anic learning and suggest that future studies employ quantitative or mixed-methods approaches across diverse educational settings to further examine the effectiveness of the Yanbu'a method.